2020
DOI: 10.1002/cac2.12002
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative diagnosis of malignant pulmonary nodules in lung cancer screening with a radiomics nomogram

Abstract: Background Lung cancer is the most commonly diagnosed cancer worldwide. Its survival rate can be significantly improved by early screening. Biomarkers based on radiomics features have been found to provide important physiological information on tumors and considered as having the potential to be used in the early screening of lung cancer. In this study, we aim to establish a radiomics model and develop a tool to improve the discrimination between benign and malignant pulmonary nodules. Methods A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 29 publications
(29 reference statements)
0
55
1
Order By: Relevance
“…In recent years, the morbidity of PTMC has dramatically increased. Studies have shown that some PTMCs can be associated with highly aggressive histological variants and even exhibit early localized invasion or lymph node and distant metastasis (36)(37)(38)(39). Unfortunately, the accuracy of diagnosing PTMC is inefficient, resulting in a proportion of patients being mistreated or misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the morbidity of PTMC has dramatically increased. Studies have shown that some PTMCs can be associated with highly aggressive histological variants and even exhibit early localized invasion or lymph node and distant metastasis (36)(37)(38)(39). Unfortunately, the accuracy of diagnosing PTMC is inefficient, resulting in a proportion of patients being mistreated or misdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…To construct the radiomics signature, a LASSO logistic regression model was used to reduce the radiomics features. This method is widely used in discriminating benign and malignant lesions (37,40,41), and it is designed to avoid overfitting (42,43). In our study, 13 radiomics features were finally selected as the most closely related features to the sub-1 cm thyroid lesion status, including 1 shape feature, 6 first order statistics features, 2 gray level dependence matrix (GLDM)-derived texture features, 2 gray level run-length matrix (GLRLM)-derived texture features, and 2 gray level size zone matrix (GLSZM)-derived texture features.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Radiomics has shown promise for extracting noninvasive radiographic virtual biopsy biomarkers. Landmark discoveries have been observed in nasopharyngeal, 12 lung, 13 breast, 14 and urinary bladder 15 cancers, demonstrating improved predictive values of multiparametric imaging features over conventional imaging metrics. We previously developed and validated a radiomicsbased nomogram to predict preoperative lymph node metastasis in patients with colorectal cancer using radiomics-derived signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) is a frontier technology adopting multiple computer algorithms to comprehensively analyze the imaging and clinicopathological data of patients for early identification of malignant nodules and decisionmaking assistance, which has achieved higher accuracy and efficiency than manual identification (9). Though the AI technique has rarely been applied to clinical decisionmaking of lung cancer, recent surge in AI algorithms has showed their potential to accurately screen malignant nodules, predict prognosis and therapeutic effect of lung cancer (10)(11)(12), indicating the potential of AI-assisted decision-making for diagnosis, prognosis, and drug efficacy prediction.…”
Section: Introductionmentioning
confidence: 99%